Moldovan perception of Greece as a tourism destination - Stela Cazacu (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: This research study analyzes Moldovans' intentions to visit Greece, and their perceptions of Greece's image as a tourism destination, according to the following dimensions: (1) environmental beauty and convenience, (2) country's citizens, (3) place and architectural structure, (4) shopping and tourist accommodation and (5) similarity of the local culture and cuisine with the Moldovan one. The goal is split into four objectives. Design/methodology/approach: For attaining the goal, a self-administered questionnaire was delivered. The empirical study was conducted in the capital of Moldova. The findings are based upon a sample of 139 respondents. Findings: The findings reveal that, overall, Greece's image as a tourist destination among Moldovan consumers is partially positive. The perceptions of the tourism dimensions were evaluated in the descending order as follows: place and architectural structure, shopping and tourist accommodation, environmental beauty and convenience, country's citizens and similarity of the local culture and cuisine with the Moldovan one. Research limitations/implications: - As it was undertaken only in the capital of Republic of Moldova and because most respondents are young people and females, the findings of this investigation do not absolutely reflect the perceptions of all Moldovans. Also, because the number of respondents is small, it is not representative of the whole Moldovan population. Hence, the results might not be very realistic and accurate. Originality/value - This study provides insightful theoretical implications and practical recommendations in creating marketing strategies that would help in managing and improving Greece's image as a destination among Moldovan tourists. Also, no study, at least to the researcher's knowledge, has evaluated Greece's image as a destination among Moldovan consumers. Finally, due to the increasing number of Moldovan tourists in Greece, it is important that Greece grasps this opportunity and positively influences the intentions of the visiting Moldovans via a positive destination image.
Keywords: M31; Z33; 330; consumer perception; destination; Greece; image; tourism